2009
DOI: 10.1055/s-2008-1027656
|View full text |Cite
|
Sign up to set email alerts
|

Russell Body Gastritis Associated with Helicobacter pylori Infection in an HIV-Positive Patient: Case Report and Review of the Literature

Abstract: In 1998 Tazawa and Tsutsumi described for the first time a case of Helicobacter pylori (HP)-related gastritis characterized by the presence of a conspicuous plasma cell infiltrate with Russell bodies, and coined the term Russell body gastritis (RBG). A 59-year-old HIV-positive man complaining of recurrent epigastric pain underwent an upper gastrointestinal endoscopy revealing in the stomach only hyperemia in the antral portion. Histology showed a moderate glandular atrophy associated with an expansion of the l… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

0
27
0

Year Published

2010
2010
2024
2024

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 28 publications
(27 citation statements)
references
References 13 publications
0
27
0
Order By: Relevance
“…The highly pathogenic Helicobacter pylori genotypes vacA and cagA may also be associated with RBG [23]. The disappearance of Russell bodies following successful Helicobacter pylori eradication therapy also supports the etiopathogenic role of the organism in RBG [1, 3, 7, 10, 11, 13, 15]. In 2006, Stewart and Spagnola reported three cases of Helicobacter -associated gastritis with crystalline plasma cell inclusions, which may represent another morphologic manifestation of immunoglobulin accumulation in response to chronic gastritis [24].…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…The highly pathogenic Helicobacter pylori genotypes vacA and cagA may also be associated with RBG [23]. The disappearance of Russell bodies following successful Helicobacter pylori eradication therapy also supports the etiopathogenic role of the organism in RBG [1, 3, 7, 10, 11, 13, 15]. In 2006, Stewart and Spagnola reported three cases of Helicobacter -associated gastritis with crystalline plasma cell inclusions, which may represent another morphologic manifestation of immunoglobulin accumulation in response to chronic gastritis [24].…”
Section: Discussionmentioning
confidence: 99%
“…Of the 20 gastric cases, 12 showed evidence of Helicobacter pylori infection; all 4 extragastric (duodenal and esophageal) cases were H. pylori negative. Other associated conditions included HIV infection [9, 11, 16, 20], ethanol abuse [1, 5], gastric carcinoma [14, 19], Barrett esophagus [22], monoclonal gammopathy of uncertain significance [8], and concurrent Hepatitis C infection and insulin-dependent diabetes mellitus [17]. …”
Section: Discussionmentioning
confidence: 99%
“…In fact, the presence of neoplastic atypical cells diffusely infiltrating the lamina propria among glandular structures may be easily misdiagnosed as a poorly differentiated carcinoma. Furthermore, even in well differentiated cases with recognizable plasma cells, the issue can be complicated by the presence of numerous Russel bodies - spherical intracytoplasmic eosinophilic immunoglobulin - containing structures, easily detectable by microscopic observation-either in association with neoplastic plasma cell proliferation, in cases of lymphoproliferative disorders displaying a certain degree of plasma cell differentiation, or in non-neoplastic, inflammatory processes characterized by a conspicuous plasma cell infiltrate, such as the so-called Russell body gastritis[3]. In such cases, plasma cells can take on the form of the signet-ring cells of poorly differentiated mucinous carcinoma of the gastrointestinal tract.…”
Section: Discussionmentioning
confidence: 99%
“…For example, H. pylori is detected in approximately two-thirds of patients with RBG [8,9,19-21,48,50,52,53,55,57,60,61]. Few other infections that have been reported with RBG include human immunodeficiency virus (three patients) [51,53,59], hepatitis C virus (one patient) [58], and candida esophagitis (one case) [49]. In addition, more than 60% of patients with RBG exhibit lesion regression following H. pylori eradication therapy [19-21,53,60].…”
Section: Intracellular Immunoglobulin Accumulation In Association Witmentioning
confidence: 99%
“…Few other infections that have been reported with RBG include human immunodeficiency virus (three patients) [51,53,59], hepatitis C virus (one patient) [58], and candida esophagitis (one case) [49]. In addition, more than 60% of patients with RBG exhibit lesion regression following H. pylori eradication therapy [19-21,53,60]. Furthermore, it has been reported that highly virulent H. pylori genotypes (vacA and cagA) are associated with the formation of Russell bodies and Mott cells in the antral mucosa [62].…”
Section: Intracellular Immunoglobulin Accumulation In Association Witmentioning
confidence: 99%